2021
DOI: 10.3389/fimmu.2020.601601
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chimeric Vaccine Against Pseudomonas aeruginosa Based on the Th17-Stimulating Epitopes of PcrV and AmpC

Abstract: Pulmonary infection caused by Pseudomonas aeruginosa (PA) has created an urgent need for an efficient vaccine, but the protection induced by current candidates is limited, partially because of the high variability of the PA genome. Antigens targeting pulmonary Th17 responses are able to provide antibody-independent and broad-spectrum protection; however, little information about Th17-stimulating antigens in PA is available. Herein, we identified two novel PA antigens that effectively induce Th17-dependent prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…By using IL-17A tracking-fate mouse models [ 42 ], CD4 + T RM cells were found derived from effector Th17 cells [ 27 ]. Our previous study found that rePcrV could induce Th17 response and enhanced protection [ 23 ]. The results of this study initially demonstrate that rePcrV intranasal immunization could induce the generation of CD4 + T RM cells secreting IL-17A in lung tissues of mice, and these cells produced a protective immune response after P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using IL-17A tracking-fate mouse models [ 42 ], CD4 + T RM cells were found derived from effector Th17 cells [ 27 ]. Our previous study found that rePcrV could induce Th17 response and enhanced protection [ 23 ]. The results of this study initially demonstrate that rePcrV intranasal immunization could induce the generation of CD4 + T RM cells secreting IL-17A in lung tissues of mice, and these cells produced a protective immune response after P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 99%
“…For pulmonary infectious diseases, mucosal immunization via the intranasal pathways is more effective than intramuscular route in inducing and stimulating immune protection of T RM [20,22]. Th17 has been regarded as a major player in the anti-P. aeruginosa immunity; indeed, in our previous study, we identified a soluble P. aeruginosa antigen called rePcrV which could induce Th17 response and provide protection against P. aeruginosa by intranasal immunization [23]. Another substrate, 1,3-β-glucan, derived from Alcaligenes faecalis, has also been reported to prompt a Th1/Th17 response [24,25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The slices were stained with hematoxylin and eosin (HE) and viewed by light microscopy at 400×magnification. Each section was given disease scores in terms of the states of hemorrhage, edema, hyperemia, neutrophil infiltration, and destruction of bronchi structure by a pathologist in a blinded fashion according to a previously reported method [ 25 ]. Each state was scored from 0 to 2 (0 = none, 2 = severe), and the final score of each section was the sum of the scores from the five states.…”
Section: Methodsmentioning
confidence: 99%
“…Therapeutic approaches independently targeting host or bacterial gene products have been largely unsuccessful likely due to bacterial metabolic adaptation to the selective pressures imposed during infection ( Opoku-Temeng et al., 2019 ; Wang et al., 2021 ; Jahantigh et al., 2022 ). It is increasingly evident that upon infection, metabolically active bacteria rapidly alter gene expression and survival strategies ( Wong Fok Lung et al., 2022 ).…”
Section: Therapeutic Targeting Of Immunometabolites In Bacterial Infe...mentioning
confidence: 99%